INDONESIA–MALAYSIA TRADE UNDER GLOBAL UNCERTAINTY AND EXCHANGE RATE VOLATILITY - Akbar Pratama Kartika; Mirzam Arqy Ahmad; Erwin Herlian; Rangga Dhia Majduddin; Haryo Bimo Budi Indrasto; Nova Widi Setyo Nugroho (EP FEB UNS, 2026)
Exchange rate uncertainty and global economic disruptions are widely recognized as key determinants of international trade flows, yet their sectoral and asymmetric dimensions remain underexplored, particularly for emerging-market bilateral trade relationships. This study examines the effects of exchange rate volatility and global crises on Indonesia–Malaysia bilateral trade at the sectoral level. Using monthly time-series data spanning January 2006 to May 2023, we employ Autoregressive Distributed Lag (ARDL) and Nonlinear ARDL (NARDL) frameworks to capture both short-run and long-run trade dynamics, as well as sector-specific asymmetric effects. Exchange rate volatility is estimated via a GARCH framework. The Global Financial Crisis (2008) and the Covid-19 pandemic (2020) are structurally identified as exogenous crisis episodes. Exchange rate volatility exerts a meaningful and persistent long-run effect on bilateral trade, confirming that price-based uncertainty is a significant driver of trade patterns. Global crises, by contrast, produce effects that are narrow, transitory, and heterogeneous across sectors. Evidence of asymmetric exchange rate effects is detected, though these effects are marginal and lack systematic consistency across sectors. Collectively, the findings suggest that bilateral trade responds more strongly to persistent exchange rate dynamics than to discrete global shocks. This study contributes to the literature by integrating sectoral disaggregation, nonlinear modeling, and structurally identified crisis periods, offering a more nuanced understanding of trade behavior under uncertainty in the context of an important South-South trading relationship.